Aberrant synaptophysin expression in classic Hodgkin lymphoma - Soyoung Im; Jeong-A. Kim; Gyeongsin Park; Uiju Cho (BMC, 2022)
Abstract Background Synaptophysin is an immunohistochemical marker for neuroendocrine differentiation and is widely used in pathologic diagnosis. Its expression in malignant lymphoma has not yet been described. However, we experienced an index case of classic Hodgkin lymphoma with synaptophysin expression. This experience prompted us to investigate synaptophysin expression in classic Hodgkin lymphoma. Method Immunohistochemical staining of synaptophysin was performed in 59 diagnosed cases of classic Hodgkin lymphoma, 10 anaplastic large cell lymphomas, 16 diffuse large B-cell lymphomas, and 5 extranodal marginal zone lymphoma of the mucosa-associated tissue. Synaptophysin-positive cases were stained for both chromogranin and CD56a. Result Of 59 classic Hodgkin lymphoma cases, 11 (19%) were positive for synaptophysin. None of the anaplastic large cell lymphomas expressed synaptophysin. Synaptophysin showed weak but specific expression in the cytoplasm of the Hodgkin lymphoma tumor cells. Other background inflammatory cells (such as macrophages, B-, and T-lymphocytes) were all negative for synaptophysin expression. Chromogranin and CD56a were not expressed in the synaptophysin-positive classic Hodgkin lymphomas. Conclusions Synaptophysin is an integral glycoprotein present in presynaptic vesicles of neurons and neuroendocrine cells. It is a diagnostic marker for neuroendocrine tumors. Aberrant synaptophysin expression has been reported in non-neuroendocrine tumors but not in lymphoma or leukemia. To the best of our knowledge, synaptophysin positivity has only been reported in a single case of precursor T-lymphoblastic leukemia/lymphoma to date. Our study showed that aberrant synaptophysin expression in classic Hodgkin lymphoma is an unexpectedly frequent finding. The mechanism underlying, and prognostic significance of, such aberrant expression is unclear. Thus, in a small biopsy, aberrant synaptophysin expression could be a diagnostic pitfall and should be carefully avoided.